Experimental Study on Engagement Characteristic of the Wet Clutch - Changliang Tang; Bokang Su; Liyong Wang; Tao Chen; Xiangliang Meng (Jixie chuandong)
The wet clutch is a key power shift component of the armored vehicle. With the increase of the speed and power density of the integrated transmission system， the engagement characteristics are closely related to the failure problems such as excessive wear of the friction pair， partial burning， and warpage of the steel sheet. For the engagement process of the wet clutch， a multi-mode loading test rig is designed and built. The mechanical inertia， eddy current dynamometer and braking device are used as the load simulation device. The engagement characteristics test of wet clutch for different speeds and control oil pressure are carried out. The corresponding stable sliding friction torque with different sliding speed and control oil pressure is measured when the load end by braking device is fixed. The corresponding dynamic and static friction coefficients are derived， which will help to further obtain the transmission characteristics of the clutch and evaluate for its service performance.